Transbahasa: Sebuah Pendekatan yang Mendukung Siswa dengan Hambatan Pendengaran - Putra, Andi Dewangga Permana (Peneliti.net, 2023)
Students with hearing impairments have common problems in everyday life regarding language and communication. This also includes the field of education where students with hearing impairments often do not have equal access to communication, both academic and non-academic. A new approach, translingualism, is seen as capable of responding to this challenge. This literature review aims to explore how this approach can be used in the pedagogical process for students with hearing impairments. A total of three studies were included in this review. The results and discussion are presented in this article